Culture and Technology: Government Strategy Ciamis Regency In Developing Digital Ecosystem Year 2023-2024 - Yuliani, Dini; Ibnu Redjo, Samugyo; Sri Kartini, Dede; Indrawati Sagita, Novie (International Proceedings of Nusantara Raya, 2024)
The development of digital technology brings both challenges and opportunities for local governments in their efforts to advance development and improve public services. Ciamis Regency as one of the regions in Indonesia responds to this dynamic by integrating local cultural elements I the digital ecosystem development strategy. This article aims to analyze the strategies implemented by the Ciamis Regency Government in building an inclusive and sustainable digital ecosystem, taking into account local socio-cultural characteristics. This research uses a qualitative approach with a case study method, through policy analysis and in-depth interviews with stakeholders in Ciamis. The results show that collaboration between the government, local communities, and the private sector plays an important role in the implementation of digital technologies that are aligned with local cultural values. In addition, the role of technology in echancing community participation and public services was identified as a key factor in the success of this strategy. The findings are expected to contribute to the development of digital policies in other regions with similar characteristics.